Unleashing local growth: The role of regional innovation and entrepreneurship in China - Jin, Zhiwei (Journal of Accounting, Business and Finance Research, 2025)
This study investigates the role of entrepreneurship and innovation in promoting local economic growth in China. Past studies have evaluated this issue using national- or province-level data. However, given China’s large size and significant diversity, even within a single province, and the fact that entrepreneurial spirit is a local issue, more localized analysis is necessary for a comprehensive understanding. Thus, using a unique dataset encompassing 286 cities from 2004 to 2020, we evaluate how entrepreneurship and innovation stimulate regional economic growth at the city-level. The results show the positive effects of entrepreneurship and innovation, particularly firm entry, outside direct investment, patent granted, and trademark registration. The study also investigates heterogeneity across administrative divisions and geographical features. Entrepreneurship and innovation are found to significantly enhance local economic development. The effects are particularly strong in provincial capitals compared to other cities. Furthermore, geographical factors, such as the Qinling-Huaihe Line and the Hu Huanyong Line, play a crucial role in shaping economic outcomes, highlighting substantial regional disparities. Entrepreneurship and innovation serve as crucial drivers of regional economic growth, but their impact varies based on administrative status and geographical context. The findings underscore the importance of localized policies that promote entrepreneurship and innovation. This study also provides valuable insights into the spatial dynamics of economic growth and contributes to the broader discourse in economic geography.